Enhancing Operational Efficiency in Cooperative: A Case Study of Koperasi Usaha Jaya Mandiri - Silaarta, Tifany Jessica; Harman, Natalia Patricia; Tedjo, Michalia Virlica; Suebu, Jerzy Valentino; Langi, Patricia Rebeca Isadella; Lelengboto, Abraham Leslie Petir (Indonesian Journal of Advanced Research, 2025)
Koperasi Usaha Jaya Mandiri is a financial institution engaged in savings and loans. In its operational activities, this cooperative still uses a manual system in recording transactions, managing member data, and preparing financial reports. This causes various problems such as the risk of recording errors, delays in the service process, and difficulties in tracking data and making reports. In addition, the manual system slows down the decision-making process due to the lack of real-time integrated data. This research aims to analyze the impact of using manual systems in cooperative operations and identify digital solutions that can improve work efficiency and effectiveness. The methods used in this research include direct observation of business processes, interviews with cooperative management and staff, and analysis of operational data. The results of this research are expected to produce an integrated information system design that is able to minimize errors, speed up the transaction process, and facilitate overall data management.